Odpowiedź:
a) [tex]2^{5} - (-2)^{5} = 32 - (-32) = 32 + 32 = 64[/tex]
b) [tex](\frac{1}{3} )^{4} + (\frac{-1}{3} )^{4} = \frac{1}{81} + \frac{1}{81} = \frac{2}{81}[/tex]
c) [tex](\frac{1}{3} )^{2} * 3^{3} = \frac{1}{9} * 27 = 3[/tex]
d) [tex]10^{3} * 0,1^{2} = 1000 * 0,01 = 10[/tex]
e) [tex]\frac{1}{3} * 3^{2} + \frac{1}{4} * 2^{2} = \frac{1}{3} * 9 + \frac{1}{4} * 4 = 3 + 1 = 4[/tex]
f) [tex]2 * 0,2^{3} - 0,2^{3} = 2 * 0,008 - 0,008 = 0,016 - 0,008 = 0,008[/tex]
g) [tex]3 *( \frac{1}{3} )^{3} + 8 * (-\frac{1}{2} )^{4} = 3 * \frac{1}{27} + 8 * \frac{1}{16} ) = \frac{1}{9} + \frac{1}{2} = \frac{2}{18} + \frac{9}{18} = \frac{11}{18}[/tex]
h) [tex](\frac{1}{2} )^{3} : (\frac{1}{6} )^{2} - (-2)^{3} =\frac{1}{8} : \frac{1}{36} - (-8) = 4\frac{1}{2} + 8 = 12\frac{1}{2}[/tex]
i) [tex](-0,1)^{4} * 20^{3} - (-2)^{4} = 0,0001 * 8000 - 16 = 0,8 - 16 = -15,2[/tex]
j) [tex](1\frac{1}{2} )^{3} : 0,5^{4} + 1,5^{1} = \frac{27}{8} : \frac{1}{16} + 1,5 = 54 + 1,5 = 55,5[/tex]
k) [tex]3^{3} - (-2)^{2} - (-1)^{6} = 27 - 4 - 1 = 23 - 1 = 22[/tex]
l) [tex](\frac{3}{5} )^{2} - \frac{3^{2} }{5} + \frac{3}{5^{2} } = \frac{9}{25} - \frac{9}{5} + \frac{3}{25} = \frac{12}{25} - \frac{9}{5} = \frac{12}{25} - \frac{45}{25} = - \frac{33}{25} = -1\frac{8}{25}[/tex]
Szczegółowe wyjaśnienie:
* - znak mnożenia